UPAYA WHO (WORLD HEALTH ORGANIZATION) DALAM MENANGGULANGI KANKER DI KOREA SELATAN MELALUI CANCER CONTROL PROGRAMME - ", Halida; Nizmi, Yusnarida Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research describes the effort of WHO (World Health Organization) within overcome cancer in Republic of Korea through it’s programme, Cancer Control Programme. Cancer main health problem in Republic of Korea. The cancer incidence and mortality number in Republic of Korea every year has been increasing. The annual number of cancer deaths has been increasing, it lead cause of death in Korea since 1983, and steadily as Korea becomes an aged society. The purpose of this study to find out the role of WHO within controlling cancer in Republic of Korea.This research is using descriptive and library research methods.The data and information obtained from books, journals and websites. This research uses pluralism perspective and international organization theory to explain effort of WHO in Republic of Korea.The result of this research shows that cancer as a world health problem makes WHO try to reduced the cancer incidence and mortality through it's program, Cancer Control Programme.This program promotes national cancer control policies plans and programmes, integrated to noncommunicable diseases and other related problems. National Cancer Control Programme is part of Cancer Control Programme which a public health programme designed to reduce the number of cancer cases and deaths. By using implementation plan, the 5-year survival rate of cancer patients in Korea has improved to 62%.Keyword : WHO, Cancer in Republic of Korea, Cancer Control Programme